Book Review: O universo conceitual de Milton Santos [The conceptual universe of Milton Santos] by Pedro de Almeida Vasconcelos. - Zanotelli, Cláudio Luiz (Geografares, 2021)
The book by Pedro Almeida Vasconcelos comes at a good time and allows us to better understand and contextualize Milton Santos’ thinking. Pedro Vasconcelos makes an exhaustive survey of the myriad of concepts and notions created by Milton Santos, demonstrating how a concept is transformed over time and has different meanings in differents works. It thus demonstrates the moving meanings of these concepts and in fact reveals that the act of thinking depends on its context and on the epistemological soil in which it emerges, derived from a certain historical situation and a certain state of the field of knowledge.